PENGARUH SOCIAL MEDIA MARKETING, CITRA MEREK, DAN PERSEPSI KUALITAS TERHADAP KEPUTUSAN PEMBELIAN BRAND FASHION LOKAL 3SECOND - Anggi Ayuning Tiyas (2022)
Based on a survey conducted by Katadata Insight Center (KIC) it shows that the largest proportion of online transactions occurs in the millennial generation aged 26-35 years. The number of product purchases that are most sought after and purchased on e-commerce, namely fashion products and accessories in 2021. It is known that currently 3second fashion products experience several phenomena that can influence product purchasing decisions, for example in terms of social media marketing used, brand image, and perceptions product quality. This research was conducted with the aim of analyzing and proving that there is an influence between social media marketing, brand image, and perceived quality on purchasing decisions. The population in this study were 3second fashion brand consumers in DKI Jakarta with a total sample of 100 respondents using non-probability sampling techniques and purposive sampling methods. This research uses quantitative methods. The software used is the SmartPLS version 3 application. The results of this study show that social media marketing, brand image, and perceived quality have a positive and significant influence on purchasing decisions for 3second local fashion brand products in DKI Jakarta.